Kekuatan Hukum Covernote Notaris sebagai Produk Hukum Notaris - Wijaya, I Gede Arya (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 4 No 1 (2019), 2019)
A notary is a public official who in principle has the authority to make authentic deeds and has other authorities as referred to in the Notary Position Act or other Laws. In addition to issuing authentic deeds, a Notary can also issue a covernote covernote as a temporary guarantee to be a temporary handle for banks to disburse credit while waiting for the related deeds to be processed by a Notary. Covernote from the process until its use involves Notary, Creditors and Debtor elements. This vacuum of norms caused the three elements to find no legal certainty rather than the strength of the law of Covernote and the vital role of covernote in the banking world so that it was necessary for a legal certainty regarding the legal power of covernote. The problem in this writing is the use of covernote Notary in the credit agreement and legal force of covernote Notary as a legal product of the Notary. This writing aims to find out the use of Covernote Notary in the credit agreement and to know the legal strength of Covernote Notary as a legal product of the Notary. The research used in this paper is the study of normative law. The use of Covernote Notary in the credit agreement is part of the Notary's business in providing certainty to the bank to be able to agree to disburse credit before the APHT is completed and the certificate of liability is issued, Notary covernote. Covernote issued by the notary is used as a guide for banks to disburse credit to debtor customers. The legal strength of Covernote as a legal product of a notary does not have any legal force, because Covernote is not an authentic deed and also not an underhanded deed, but only an ordinary letter which only explains the Notary's statement to explain that the thing that the Notary is working is still not finishe. Notaris merupakan pejabat umum yang pada prinsipnya memiliki kewenangan dalam membuat akte autentik dan kewenangan yang lainya seperti dalam UU Jabatan Notaris atau Undang – Undang lainya. Selain mengeluarkan akta autentik, seorang Notaris juga dapat mengeluarkan covernote. Covernote ini dijadikan sebagai jaminan untuk menjadi pegangan sementara bagi bank guna mencairkan kredit sembari menunggu akta-akta terkait selesai diproses oleh Notaris. Covernote dari proses hingga penggunaanya melibatkan unsur Notaris, Kreditur dan Debitur. Kekosongan norma (vacum of norm) ini menyebabkan ketiga unsur tersebut tidak mendapati kepastian hukum dari kekuatan hukum Covernote tersebut. Begitu vitalnya peran covernote dalam dunia perbankan sehingga perlu atas suatu kepastian hukum mengenai kekuatan hukum covernote. Permasalahan dalam penulisan ini adalah penggunaan covernote Notaris dalam perjanjian kredit dan kekuatan hukum covernote Notaris sebagai produk hukum Notaris. Penulisan ini bertujuan mengetahui penggunaan Covernote Notaris dalam perjanjian kredit dan mengetahui kekuatan hukum Covernote Notaris sebagai produk hukum Notaris. Penelitian ini menggunakan peneliltian hukum normatif. Penggunaan Covernote Notaris dalam perjanjian kredit adalah bagian dari usaha Notaris dalam memberikan kepastian kepada pihak bank untuk bisa menyetujui mencairkan kredit sebelum pembuatan APHT selesai dan sertifikat hak tanggungan terbit, Notaris covernote. Bank dapat menjadikan Covernote sebagai pegangan untuk mencairkan kredit. Kekuatan hukum suatu Covernote sebagai produk hukum notaris tidaklah memiliki kekuatan hukum apapun, karena Covernote bukan akta autentik dan juga bukan akta dibawah tangan, melainkan hanya surat biasa yang hanya menjelaskan  pernyataan Notaris untuk menerangkan bahwa hal yang Notaris kerjakan masih belum selesai